Strongyloides stercoralis Presenting as Diffuse Alveolar Hemorrhage in a Lupus Nephritis Patient - Rojashree Gundu; Ritesh Kumar; Urmila Anandh (Indian Journal of Kidney Diseases)
Strongyloidiasis is a parasitic disease caused by Strongyloides stercoralis (SS), a nematode predominately endemic to the tropical and subtropical regions. Autoinfection enables the organism to infect the host for extended periods. Symptoms, when present, are nonspecific and may initially lead to misdiagnosis, particularly if the patient has additional comorbid conditions. Immunosuppressive states place patients at risk for strongyloides hyperinfection syndrome, whereby the organism rapidly proliferates. Unfortunately, the nonspecific presentation of strongyloidiasis often leads to delays in diagnosis and treatment. We describe an unusual case of SS hyperinfection in a 34-year-old female with a long-standing history of lupus nephritis Class V on treatment, who presented to us with diffuse alveolar hemorrhage. The diagnosis was rendered on the identification of numerous organisms during histologic examination of the bronchoalveolar lavage specimen. Despite specific anti-infective treatment, the patient succumbed to her illness.